DESAIN PENGEMBANGAN PENDIDIKAN INKLUSI DI SEKOLAH DASAR SANTA ANGELA BANDUNG - Sirajuddin Azhar (STKIP Subang, 2022)
ABSTRACT Elementary school is a level of education that has the goal of equipping students in terms of basic skills to develop their lives as human beings who have a single personality or individual, as members of society, and as citizens. Education is not only needed by normal individuals but also those with special needs. At Santa Angela school, it has implemented inclusive education and it needs the development of inclusive education so that the learning of students with special needs goes well. This research uses the R&D method, which is the process by collecting data and developing inclusive education designs. Collecting data by observing schools to find out information on the inclusive education system in schools and looking for what needs to be developed in these schools. researchers made an inclusive education design in terms of facilities, curriculum and costs. ABSTRAK Sekolah dasar adalah jenjang pendidikan yang memiliki tujuan membekali siswa dari segi kemampuan dasar guna mengembangkan kehidupannya sebagai manusia yang memiliki kepribadian atau individu tunggal, sebagai anggota dalam masyarakat, dan merupakan warga negara. Pendidikan tidak hanya dibutuhkan oleh individu yang normal tetapi juga yang berkebutuhan khusus. Di sekolah santa Angela sudah menerapkan Pendidikan inklusi dan dibutuhkan pengembangan Pendidikan inklusi agar pembelajaran peserta didik ABK berjalan dengan baik. Penelitian ini menggunakan metode R&D, yang mana prosesnya dengan pengumpulan data dan pengembangan desain Pendidikan inklusi. Pengumpulan data dengan melakukan observasi ke sekolah untuk mengetahui informasi system Pendidikan inklusi di sekolah dan mencari apa saja yang harus dikembangkan di sekolah tersebut. peneliti membuat desain Pendidikan inklusi segi fasilitas, kurikulum dan biaya